Sizing up the samples: evaluating packaging waste generated by cosmeceutical products. (17th January 2023) - Duff, Eimear; Gilhooley, Eimear; Feighery, Cliona
Abstract : We examined the avoidable plastic waste generated by miniature samples of nonprescription topical cosmeceutical products. Smaller samples may not offer patients an adequate trial of a product, may relate to products that are more expensive for patients, and create proportionally more waste than full-size products. In light of the pressing need to reduce carbon emissions, companies should be proactive in reducing plastic waste, while dermatologists should consider the environmental, ethical and economic impact of the cosmeceutical products they may offer as samples to patients.